Lived experiences of matrilocal husbands in Filipino marriage patterns: a phenomenological inquiry - Fernando, Daniel (Technium Social Sciences Journal, 2024)
Marriage exists to bring a man and a woman together as husband and wife. Hence, determining a community’s rules or rules of residence in marriage has long been established as an essential requirement in understanding the social system. Moreover, in-residence practices are the first family pattern to exhibit change and cause subsequent change; thus, they warrant attention. Meanwhile, when couples marry, they usually live in or near the home of the man’s parents. However, sometimes, this wasn’t practiced because of the preeminence of the bride’s family. Hence, unlike the more common patrilocal marriage, the groom resides with the bride’s parents. A phenomenological qualitative study was utilized to understand the lived experiences of matrilocal husbands in Filipino marriage patterns. The researcher identified four major themes from the transcripts using Colaizzi’s phenomenological data analysis procedure. Reasons for becoming a matrilocal husband are primarily based on the socioeconomic status of the couple. The participants expressed that there were moments of self-adjustment and set-aside decisions. They expressed a need to socialize, particularly with his in-laws. This study can be used for policy-making, specifically for the local government unit, to extend activities to cater to the personal, social, and psychological impacts of being a matrilocal husband. It can also be integrated into gender and society courses in college.